2017
DOI: 10.3389/fchem.2017.00055
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Acylglycerols Composition, Quality Characteristics and In vivo Effects of Dietary Pumpkin Seed Oil upon Thermal Oxidation

Abstract: This study was aimed to determine the acylglycerols composition, quality characteristics, and protective role of dietary pumpkin seed oil (PSO) in rabbits. PSO was thermally oxidized and analyzed for quality characteristics and acylglycerols composition using reversed phase high performance liquid chromatography with diode array detection (HPLC-DAD). Oxidized and un-oxidized oil samples were fed to the rabbits in different doses for 2 weeks. The changes in the serum biochemistry, hematology, and liver histolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
6
0
2
Order By: Relevance
“…Estrogen plays a pivotal role not only in the reproductive system but also in certain vital health condition (Makni et al, ). Estrogen deficiency will undoubtedly cause several physiological changes and pathological conditions, such as osteoporosis, cardiovascular diseases, dyslipidemia, sleep disorders, and joint pain (Gossell‐Williams, Lyttle, Clarke, Gardner, & Simon, ; Zeb & Ahmad, ). Therefore, several efforts should be made to maintain estrogen levels within the female body.…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen plays a pivotal role not only in the reproductive system but also in certain vital health condition (Makni et al, ). Estrogen deficiency will undoubtedly cause several physiological changes and pathological conditions, such as osteoporosis, cardiovascular diseases, dyslipidemia, sleep disorders, and joint pain (Gossell‐Williams, Lyttle, Clarke, Gardner, & Simon, ; Zeb & Ahmad, ). Therefore, several efforts should be made to maintain estrogen levels within the female body.…”
Section: Introductionmentioning
confidence: 99%
“…The bands intervals the in the tracks are placed in agreement to the increase of the band values with Rf between the sample application site (value 0.0) and the solvent front at the end of the development (value 1.0). Subsequently, in the calibration mode of bands in linear function, the main reference TG (18:2/18:2/18:2) was observed in most pumpkin seed extracts (Zeb & Ahmad, 2017). The baseline of all leads was defined to display them in the form of a chromatogram.…”
Section: Gelanalyzer Plate Analysismentioning
confidence: 99%
“…Wild pumpkin species TG profile has been established to date (Ali et al, 2017;Azimova, Glushenkova, & Vinogradova, 2011;Neđeral et al, 2012;Zeb & Ahmad, 2017), although there is no comparison of TG composition in domesticated versus wild pumpkin seeds. Some of the methods for the study of TG profile in pumpkins comprise: the use of silica gel plates impregnated with silver nitrate and subsequent evaluation of the fatty acid methyl esters by gas chromatography/mass spectrometry (GC/MS) (Yoshida et al, 2004); the carbon equivalent number (ECN42), International Olive Council (IOC) chromatographic method (Bardaa et al, 2016); the high performance liquid chromatography (HPLC) in its modalities (Ali et al, 2017;Zeb & Ahmad, 2017). and laser-assisted matrix desorption-ionization time-of-flight (MALDI-TOF-MS) (Beneito et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further study revealed that pumpkin seeds exhibited estrogenic-like effects such as regulating lipid metabolism, bone remodeling, mammary gland and uterus epithelial cells development. Phytoestrogen components were the key role in inhibiting cardiovascular outcomes and balancing the plasma lipids level such as total cholesterol, low-density lipoprotein (LDL), highdensity lipoprotein (HDL), and triglyceride (Gossell-Williams, et al, 2008;Jones, et al, 2000;Zeb and Ahmad, 2017). In conclusion, phytoestrogens and tocopherols presented in pumpkin seeds contribute to their estrogenic-like effects.…”
Section: Estrogenic-like Effectsmentioning
confidence: 99%